Evaluation of the insecticidal potential of leaf extracts of Anadenanthera colubrina var. cebil (Griseb) Altschul against Tetranychus urticae Koch and Sitophilus zeamais Mots - Silva-Bessa, Cibele Maria Alves da; Mercês, Paula Fernanda Figueiredo das; Malafaia, Carolina Barbosa; Napoleão, Thiago Henrique; Silva, Milena Martins Correia da; Câmara, Cláudio Augusto Gomes da; Correia, Maria Tereza dos Santos; Silva, Márcia Vanusa; Oliva, Maria Luiza Vilela (Journal of Environmental Analysis and Progress, 2019)
The deterioration and degradation of crops by insects causes economic losses of several billion dollars and affects food security. Sitophilus zeamais and Tetranychus urticae are two economically important species of agricultural crops around the world. The high toxicity of synthetic insecticides and the development of insect resistance to currently used chemicals stimulate the investigation of plant-derived insecticides as new alternatives for pest control. The insecticidal properties of secondary metabolites have been recognized, and have been confirmed scientifically in the last decades. The extract in cyclohexane (Ch) and ethyl acetate (Ea) of the leaves of Anadenanthera colubrina var. cebil collected in the dry and rainy seasons were evaluated for the survival and nutritional physiology of S. zeamais (maize weevil) and for the acaricidal effect front T. urticae (two-spotted spider). All extracts induced mortality of S. zeamais; however, only cyclohexane dry season (Chd) and ethyl acetate in the rainy season (Ear) caused significant mortality (p <0.05), more than 50%, promoting physiological damage to insects in all concentrations tested. In the mortality tests with the spider mite, extracts Chd and Ear showed an LC50 of 52.75 and 156.42 mg.mL-1. Still, in the same test, it can be observed that oviposition was also susceptible to extracts. Therefore, the extracts of A. colubrina are a source of compounds capable of interfering with and impairing the metabolism of the two studied pests.